EFEKTIVITAS FINGERPRINT DALAM MENINGKATKAN DISIPLIN PEGAWAI DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN MUSI BANYUASIN PROVINSI SUMATERA SELATAN - Putra, Thomy Wahyudi Ade; Madjid, Udaya (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2019)
This research was conducted to find out the fingerprint usage and how effective fingerprint in improving employee’s discipline in the Department of Investment and Integrated Services One Door (DPM-PTSP) of Musi Banyuasin Regency. Also to find out the obstacles and efforts that have been made in improving employee’s discipline. This research based on an inductive approach with descriptive methods. the data collection techniques used are interviews, observations and documentation. Tangkilisan (2005:141) there are 4 effectiveness evaluation, there are target achievement, adaption capability, job satisfaction and responsibility. Fingerprint usage has been functioned well to improve employee’s discipline and organizatinal performance. There are some obstacles which are the employee’s that came for fingerprint, not performance oriented so the employees can’t finished the tasks not on time. The efforts that have been made by DPM-PTSP Musi Banyuasin regency is direct control by leader and punish firmly and objectively based on procedure. Recommendation from writer is to improve technology in fingerprint machine, the scanner sensitiveness in reading the fingerprints and to add another one unit of fingerprint machine.